2007
DOI: 10.1101/lm.394707
|View full text |Cite
|
Sign up to set email alerts
|

Aging affects motor learning but not savings at transfer of learning

Abstract: Two important components of skill learning are the learning process itself (motor acquisition) and the ability to transfer what has been learned to new task variants (motor transfer). Many studies have documented age-related declines in the ability to learn new manual motor skills. In this study, I tested whether the degree of savings at transfer of learning is similarly affected by advancing age. Young and older adults made aiming movements with a joystick to hit targets presented on a computer screen, with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
59
5
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 36 publications
13
59
5
3
Order By: Relevance
“…This deficit becomes progressively evident with increasingly complex motor tasks (YORDANOVA et al, 2004). Another study found motor acquisition deficit in older adults; however, they exhibit normal transfer of learning, indicating that motor acquisition and transfer are distinct processes, affected differently by age (SEIDLER, 2007). All the results found to date show that the causes of reduced motor learning are multifactorial.…”
Section: Introductionmentioning
confidence: 70%
“…This deficit becomes progressively evident with increasingly complex motor tasks (YORDANOVA et al, 2004). Another study found motor acquisition deficit in older adults; however, they exhibit normal transfer of learning, indicating that motor acquisition and transfer are distinct processes, affected differently by age (SEIDLER, 2007). All the results found to date show that the causes of reduced motor learning are multifactorial.…”
Section: Introductionmentioning
confidence: 70%
“…This may increase the accurate diagnosis of MCI among elderly population with low levels of education. These data add to the growing literature examining the relationships between sensorimotor and cognitive function decline with aging [35,36,37,38,39,40]. …”
Section: Discussionmentioning
confidence: 90%
“…These interactions between experiences can be positive or negative, and were studied extensively in connection with education, psychology, and motor learning, but very little is known about the relevant neuronal substrates (Seidler 2007). From a temporal perspective, learning can be divided into an immediate "on-line" acquisition phase and an "off-line" consolidation phase (Balas et al 2007).…”
mentioning
confidence: 99%